Masalah Globalisasi di Indonesia: Antara Kepentingan, Kebijakan, dan Tantangan - Paulus Rudolf Yuniarto (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2014)
There are two fundamental issues facing globalization problem todays, namely the economic competition and the threat of the nations unity as the question of regional conflict. Indonesia, in this context, is expected more conscious and aware to various challenges of globalization. To respond the globalization challenges, since 2006, through a variety of research from research centers under Social and Humanities Deputies, Indonesia Institute of Science has addressed these challenges. Through a study of literature on all those conducted research, the availability of information and the institutional arrangement for the stakeholders (local and national) with reference to globalization problem has still become a fundamental issue. This paper aimed to recommendation policy on globalization in Indonesia, regarding the need for cooperation in the form of joint ventures and strategic alliances between governments, transnational actors and civil society. Al those stakeholder are required to and obliging in order to face competition and also as part of disputes solutions as well as capacity building to prepare rough leader cadres. The Government could facilitate such efforts.Keywords: Globalization, Stakeholder, Policy, Challenges